Investigating the roles prion-like domains play in cellular stress responses - Shattuck, Jenifer Elizabeth, author; Ross, Eric, advisor; Peersen, Olve, committee member; Di Pietro, Santiago, committee member; Telling, Glenn, committee member (Colorado State University. Libraries, 2018)
Prion-like domains are involved in the formation of either functional or pathogenic protein aggregates. These aggregates play an important role in regulating a broad-range of cellular functions. In the budding yeast Saccharomyces cerevisiae, at least 10 proteins have been identified that form self-propagating amyloid-based prions. Most known yeast prion proteins contain a low-complexity, intrinsically-disordered prion-forming domain that is converted into stable, detergent-insoluble aggregates, necessary for prion activity. These prion-forming domains tend to be glutamine/asparagine (Q/N) rich, and relatively lacking in charged and hydrophobic amino acids. To better understand the amino acid sequence features that promote prion activity, we used the prediction algorithm PAPA to identify predicted aggregation-prone prion-like domains (PrLD). While from this study we did not identify new yeast prion proteins, we identified several PrLDs with aggregation activity. Therefore, in follow up studies we investigated the role these PrLDs play in other protein assemblies involved in cellular stress responses. First, we investigated how a prion-like protein kinase, Sky1, plays a role in regulating stress granules. Stress granules are cytoplasmic assemblies that form when translation initiation is limiting, including under a variety of stress conditions. Because these cytoplasmic granules are important regulatory machinery for cellular homeostasis, mutations that increase stress granule formation or decrease clearance have been linked to various neurodegenerative diseases. We provided evidence that Sky1 is recruited to stress granules through its aggregation-prone PrLD, and it phosphorylates an RNA-binding protein to efficiently disassemble stress granules. Additionally, we showed when Sky1 is overexpressed it can compensate for defects in other disassembly pathways. These findings contribute to understanding the regulation of stress granules, and provides a possible mechanism to mitigate persistent stress granules in neurodegenerative diseases. Next, we investigated how PrLDs are used to assemble and activate a vacuole-signaling complex. Many cellular processes are regulated primarily through the production of phosphoinositides. Specifically, synthesis and turnover of phosphatidylinositol 3,5 bisphosphate (PtdIns(3,5)P2) is regulated by a vacuole-signaling complex, containing prion-like proteins Fab1, Vac7, and Vac14. Interestingly, during hyperosmotic stress, there is a rapid and dramatic rise in PtdIns(3,5)P2, which leads to vacuole remodeling, critical for cellular survival. We used aggregation-altering mutations to characterize the role of Fab1's PrLD in response to osmotic stress. Overall, these studies provided evidence that Fab1's activation requires its aggregation prone PrLD for recruitment and efficient activation for cellular adaptation to stress. Collectively, the studies described below provide insights into the diverse roles PrLDs play in regulating cellular stress responses. Moreover, these studies have contributed to the field of aggregation-mediated cellular regulation by identifying new proteins involved, new proposed mechanisms, and new insights into the cellular consequences that arise from perturbations in regulation of these processes.
Keywords: protein aggregation; yeast prions; stress granules; neurodegenerative disease